2020
DOI: 10.1038/s41598-020-62108-6
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide identification, characterization and functional analysis of salt-related long non-coding RNAs in non-model plant Pistacia vera L. using transcriptome high throughput sequencing

Abstract: Long non-coding RNAs (lncRNAs) play crucial roles in regulating gene expression in response to plant stresses. Given the importance regulatory roles of lncRNAs, providing methods for predicting the function of these molecules, especially in non-model plants, is strongly demanded by researchers. Here, we constructed a reference sequence for lncRNAs in P. vera (Pistacia vera L.) with 53220 transcripts. In total, we identified 1909 and 2802 salt responsive lncRNAs in Ghazvini, a salt tolerant cultivar, after 6 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 146 publications
(110 reference statements)
0
24
0
Order By: Relevance
“… Salinity lncRNA TCONS_00020253 Medtr1g081900 and Salinity TCONS_00116877 Medtr7g094600 Salinity Arabidosis DRIR ANNAT7,NAC3 and Affecting fucosyltransferase or [ 37 ] WRKY8 NAC3 transcription factor Salinity Cotton SN91–11 lnc_388,lnc_883, Gh_A09G1182, Targeting Gh_A09G1182, [ 86 ] Gh_D03G0339 genes lnc_973 and lnc_253 and Gh_D03G0339 genes Regulating ghr-miR399 and ghr-156e by eTM Salinity Poplar P. euphratica Peu_00167161, Pal_00184400 HKT1 P.alba var. pyramidalis Pal_00132209 fucosyltransferase or NAC3 Salinity Cotton SN91–11 lncRNA973 SOD, CAT, POD and P5CS, lncRNA973 regulate the [ 105 ] RBOHB, RBOHD, NHX7 ghr-miR399 and its target gene GhPHO2 MYB5, WRKY46, ERF62, NAC29 Salinity Pistacia vera L. Ghazvini and Sarakhs 5 NAT-lncRNAs CERK1, LEA, Laccase genes NAT-lncRNA regulate ATPase, [ 106 ] TF genes, ...…”
Section: Introductionmentioning
confidence: 99%
“… Salinity lncRNA TCONS_00020253 Medtr1g081900 and Salinity TCONS_00116877 Medtr7g094600 Salinity Arabidosis DRIR ANNAT7,NAC3 and Affecting fucosyltransferase or [ 37 ] WRKY8 NAC3 transcription factor Salinity Cotton SN91–11 lnc_388,lnc_883, Gh_A09G1182, Targeting Gh_A09G1182, [ 86 ] Gh_D03G0339 genes lnc_973 and lnc_253 and Gh_D03G0339 genes Regulating ghr-miR399 and ghr-156e by eTM Salinity Poplar P. euphratica Peu_00167161, Pal_00184400 HKT1 P.alba var. pyramidalis Pal_00132209 fucosyltransferase or NAC3 Salinity Cotton SN91–11 lncRNA973 SOD, CAT, POD and P5CS, lncRNA973 regulate the [ 105 ] RBOHB, RBOHD, NHX7 ghr-miR399 and its target gene GhPHO2 MYB5, WRKY46, ERF62, NAC29 Salinity Pistacia vera L. Ghazvini and Sarakhs 5 NAT-lncRNAs CERK1, LEA, Laccase genes NAT-lncRNA regulate ATPase, [ 106 ] TF genes, ...…”
Section: Introductionmentioning
confidence: 99%
“…Differentially expressed coding or non-coding transcripts between tolerant and sensitive pistachio genotypes can be used to design FMs for more efficient salt tolerance screening and identifying successful salt tolerance mechanisms of tolerant genotypes 12 . In the present study, for the very first time, the SSR motifs in the specific early and late salt responsive genes of tolerant pistachio genotype were used for designing ISSR primers (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Comparative genomic analysis revealed that stress tolerance of P. vera is probably due to the chitinase gene families, and the expanded cytochrome P450 11 . Recently, the identification and characterization of long noncoding RNAs (lncRNAs) showed that these molecules act as transcriptional and post-transcriptional regulators by regulating the expression of transcription factor genes such as MYB , NAC , WRKY , ZIP , TCP and GRAS and several genes such as ATPase , LEA , Laccase , CERK1 and UGT in response to salt stress condition for pistachio adaptation 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…chinensis [ 40 ], Cucumis sativus [ 41 ], and Brassica juncea [ 42 ], however, the regulation of lncRNA expression by bZIP TFs under heat stress has not been reported yet. On the contrary, bZIP TFs were already reported to be targets of stress-regulated lncRNAs in Pistacia vera [ 43 ] and in Cleistogenes songorica [ 44 ]. Finaly, the lack of consistency among upregulated genes and a reasonable coherence among the downregulated genes, together with the upregulation of numerous lncRNAs suggests the possible mechanism of the upregulation of the downstream stress-responsive genes via lncRNAs alongside their direct transcription regulation.…”
Section: Discussionmentioning
confidence: 99%